Manajemen Perawatan Mesin Genset Gedung Plaza Mandiri Menggunakan Metode Realibility Centered Maintenance dan Maintenance Value Stream Map - Raka Pratama Putra; Asep Endih Nurhidayat (Publikasi Indonesia, 2022)
To find out the right action for the maintenance of the generator engine components at the Plaza Mandiri Building, to reduce activities that do not add value to the maintenance process on the generator engine, and to find out and analyze the significance of the influence of the RCM (Realibility Centered Maintenance) and MVSM (Reliability Centered Maintenance) methods. The Maintenance Value Stream Map method) on the maintenance management of the Plaza Mandiri Building generator engine. The research method used is the RCM (Reliability Centered Maintenance) and MVSM (Maintenance Value Stream Map Method). The data used are primary data and secondary data sourced from PT. Exim Bank Building. There are activities that do not add value to the maintenance process on the generator engine. Non-value added activities that do not add value to the maintenance process on the generator engine are oil filter replacement 95 minutes, oil filter cleaning 62 minutes, fan belting replacement 89 minutes, air filter replacement 98 minutes, air filter cleaning 72 minutes, diesel filter replacement 93 Minutes, diesel filter cleaning 67 Minutes, radiator air filter replacement 85 Minutes, radiator air filter cleaning 59 Minutes, dynamo starter replacement 97 Minutes, generator battery replacement 83 Minutes, fuse replacement 83 Minutes, oil tank cleaning 107 Minutes. RCM and MVSM can solve problems in the maintenance management of the generator set at the Plaza Mandiri Building by producing a generator engine maintenance schedule which is divided into two, namely, a component check schedule and a component replacement schedule.